The fly that poisons Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Of the 42 poorest countries on the planet, 32 are African and play unwilling host to an uninvited guest the tsetse fly, which transmits the trypanosome parasite to humans and livestock alike, resulting in sleeping sickness or trypanosomiasis. In Afric